Morte na antilírica de João Cabral de Melo Neto - Borsato, Fabiane Renata [UNESP] (My University, 2010)
The critic João Alexandre Barbosa, points in the work Agrestes (1981-1985), of the Brazilian poet João Cabral de Melo Neto, the presence of individualized death. Thus way, this study proposes to analyse the meanings of lyrism and first-person enunciations, in the work Agrestes, a trace gradually eliminated from Cabral’s discursive field since his first work, Pedra do Sono (1940-1). These elements will clash with João Cabral’s poetics, previously based on the selection of voices and artistic practices consistent with his compositional method, with rigorous sorting values and elimination of any subjectivism. To understand this inconsistency, we propose studying the last part of the work Agrestes, entitled “A indesejada das gentes”, a place where the theme of death is recurrent, as well as the presence of enunciators to set out, even to reveal its feelings about aging and death. The analytical procedure should research the hypothesis of rupture of the inflexible tone of João Cabral’s speech that would follow in respect to the poetic project, a reverse path, starting from objective poetry in the direction of subjective poetry.
The death in João Cabral de Melo Neto’s anti-lyric poetry
Keywords: João Cabral de Melo Neto; Agrestes; Death; Brazilian poetry; Lyrism; João Cabral de Melo Neto; Agrestes; Poesia Brasileira